Clonal evolution of AML1-ETO coexisting with BCR-ABL and additional chromosome abnormalities in a blastic transformation of chronic myeloid leukemia - Ma, Cheng-Cheng (J Int Med Res, 2020)
Blast crisis develops in a minority of patients with chronic myeloid leukemia even in the era of tyrosine kinase inhibitor (TKI) therapy. Reports suggest that we know little about the mechanism of BCR-ABL and AML1-ETO co-expression in blast crisis of chronic myeloid leukemia, and that other chromosomal abnormalities also coexist. Here, we document an unusual and interesting case of a 51-year-old female diagnosed in the chronic phase of chronic myeloid leukemia. After undergoing TKI treatment for 3 months, her bone marrow aspirates in the chronic phase had transformed to blast crisis. Molecular genetic testing indicated she was positive for p210 form of BCR-ABL (copy number decreased from 108.91% to 56.96%) and AML1-ETO fusion (copy number, 5.65%) genes and had additional chromosomal abnormalities of t(8; 21)(q22; q22)/t(9; 22)(q34; q11), t(2; 5)(p24; q13) and an additional +8 chromosome.